Kedudukan Teori dalam Struktur Ilmu Hukum - Nurul Qamar (SIGn Jurnal Hukum, 2021)
This study aims to explain the theory position in the structure of legal science. This research is a normative legal research. The data collection technique used is literature study. The data that has been collected is then processed in a qualitative descriptive manner, then described in a narrative manner. The results of the study indicate that legal theory is one of the theoretical disciplines, whose object of study is law in a broad sense. The legal theory does not study law in a dogmatic definition and does not examine law in a positive law sense but explores legal science in a broader sense. The legal theory examines legal science from a critical, concrete, and analytical perspective so that the approach is interdisciplinary and multidisciplinary. Legal theory is a more in-depth approach to legal science in positive legal science approaches and legal dogmatics. Therefore, legal theory is positioned as a meta-theory of the science of law theory as a positive legal theory and legal dogmatics.